2016
DOI: 10.1007/s13593-015-0342-x
|View full text |Cite
|
Sign up to set email alerts
|

Weed-insect pollinator networks as bio-indicators of ecological sustainability in agriculture. A review

Abstract: The intensification of agricultural practices contributes to the decline of many taxa such as insects and wild plants. Weeds are serious competitors for crop production and are thus controlled. Nonetheless, weeds enhance floral diversity in agricultural landscapes. Weeds provide food for insects in exchange for pollination. The stability of mutualistic interactions in pollination networks depends on conservation of insect pollinator and weed communities. Some agricultural practices can destabilize interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 246 publications
(271 reference statements)
5
73
0
2
Order By: Relevance
“…We also found that oligolectic species were associated with landscapes with low cover and high fragmentation of woodlands, which contradicted our expectations. This trend may be explained by the fact that the oligolectic species we captured in the southwest France sites were dominated by species from the Andrena and Eucera genera, foraging principally on plants in the Brassicaceae and Fabaceae respectively, which can be easily found in the crop mosaic, as mass‐flowering crops (oilseed rape) or weed species (clover or mustard) (Le FĂ©on et al , Bretagnolle and Gaba , Rollin et al ). As woodland and annual crop proportions were negatively correlated in the French landscapes (r = –0.55, p < 0.0001), oligolectic species were less abundant in wooded landscapes, presumably because they found fewer suitable floral resources than in less wooded landscapes.…”
Section: Discussionmentioning
confidence: 97%
“…We also found that oligolectic species were associated with landscapes with low cover and high fragmentation of woodlands, which contradicted our expectations. This trend may be explained by the fact that the oligolectic species we captured in the southwest France sites were dominated by species from the Andrena and Eucera genera, foraging principally on plants in the Brassicaceae and Fabaceae respectively, which can be easily found in the crop mosaic, as mass‐flowering crops (oilseed rape) or weed species (clover or mustard) (Le FĂ©on et al , Bretagnolle and Gaba , Rollin et al ). As woodland and annual crop proportions were negatively correlated in the French landscapes (r = –0.55, p < 0.0001), oligolectic species were less abundant in wooded landscapes, presumably because they found fewer suitable floral resources than in less wooded landscapes.…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, arable plants colonized European landscapes earlier than 'natural elements' such as Fagus sylvatica (the spread of which may have also been decisively favoured by human land use (Magri 2008)). Considering this status and their key functions in agroecosystems, such as habitat or food provision for beneficial fauna (Franke et al 2009;Rollin et al 2016), the inclusion of rare arable plants in such lists seems justified. Recent studies on the threat to segetal species in southern and southeastern Europe (Hulina 2005;Pinke et al 2011;RotchĂ©s-Ribalta et al 2015a) indicate an increasing awareness of the issue there.…”
Section: Specific Characteristics Of Rare Arable Plantsmentioning
confidence: 99%
“…Crop yields improve with increased pollinator functional diversity (Hoehn et al 2008), fruit and seed set improve when wild bees are present (Garibaldi et al 2013;Campbell et al 2017), and due to the loose pollen held on body hairs, individual visits by solitary bees often transfer more pollen than visits by honey bees (Woodcock et al 2013). Additionally, wild bees are important for the pollination of wildflowers (Forup and Memmott 2005;Biesmeijer et al 2006;Rollin et al 2016), with some rarer wildflower species relying on specific native bees to ensure their survival (Gibson et al 2006), and there is evidence that wildflowers might not be adequately pollinated with decreased pollinator abundance (Jacobs et al 2009). It is therefore vital we maintain our wild bee populations to ensure the continued pollination of our crops and wildflowers.…”
Section: Introductionmentioning
confidence: 99%